The Realities of Government Construction Projects in Nepal: Systemic Inefficiencies and Challenges - Gautam, Rijan; Shakya, Ashmita; Kadariya, Sushil (Journal of Himalaya College of Engineering, 2025)
Nepal, a developing and landlocked country with diverse geography and challenging terrain, relies heavily on infrastructure development to enhance regional connectivity and stimulate economic growth. However, government-led construction projects often suffer from systemic inefficiencies rooted in political instability, poor governance and bureaucratic hurdles. Frequent changes in government disrupt policy continuity and delay crucial decision-making processes, resulting in stalled project approvals and implementation gaps. Political interference in project selection, contract awarding and staffing contributes to favoritism and reduces accountability. Additionally, excessive bureaucratic procedures and weak institutional coordination lead to significant time delays, cost overruns and compromised construction quality. These challenges not only waste public resources but also hinder access to essential infrastructure, slowing down national development. This paper critically examines these effects and highlights the urgent need for policy reform, improved institutional capacity, and political stability to ensure successful infrastructure delivery in Nepal.